128 Implications of lowering the threshold of cardiac troponin in the diagnosis of myocardial infarction. (16th May 2012) - Lee, K K; Mills, N L; McAllister, D A; Churchhouse, A M D; MacLeod, M; Stoddart, M; Walker, S; Denvir, M A; Fox, K A A; Newby, D E
Abstract : Introduction: The Universal Definition recommends the 99 percentile of cardiac troponin as the diagnostic threshold for myocardial infarction (MI) in patients with suspected acute coronary syndrome if the assay achieves a coefficient of variation (CV) <10%. However, due to imprecision in contemporary assays and concern of over diagnosing myocardial infarction, diagnostic thresholds are currently set at higher concentrations where the assay can achieve CV ≤10%. The aim of this study was to assess the relationship between plasma troponin I concentrations, assay precision and clinical outcomes in patients with suspected acute coronary syndrome. Methods: Using a contemporary sensitive troponin I assay, consecutive patients admitted with suspected acute coronary syndrome (n=2092) were stratified according to the 99th percentile (0.012 ng/ml; CV 20.8%) and current diagnostic threshold (0.05 ng/ml; CV 7.2%) into three groups: <0.012 ng/ml, 0.012–0.049 ng/ml and ≥0.05 ng/ml. Event-free survival (recurrent myocardial infarction or death) at 1 year was compared between patients grouped by troponin I concentration. Results: Plasma troponin concentrations were <0.012 ng/ml in 988 patients (47%), 0.012–0.049 ng/ml in 352 patients (17%) and ≥0.05 ng/ml in 752 patients (36%). At 1 year, patients with troponin concentrations 0.012–0.049 ng/ml were more likely to be dead or readmitted with recurrent myocardial infarction compared to those with troponin concentrations <0.012 ng/ml (13% vs 3%; OR 4.8, 95% CI 3.0 to 7.7; p<0.001). Compared to troponin ≥0.050 ng/ml, patients with troponin 0.012–0.049 ng/ml had a higher risk profile but were less likely to be diagnosed with, or investigated and treated for, acute coronary syndrome. Conclusions: Lowering the diagnostic threshold to the 99th percentile and accepting greater assay imprecision would identify those at high-risk of recurrent MI and death, but increase the diagnosis of MI by 46%. It remains to be established whether reclassifying and treating these patients as MI would improve outcome.